Efektivitas Bauran Promosi dalam Meningkatkan Volume Penjualan di Art Shop Sukarara Lombok Tengah - Lale Puspita Kembang; Rian Indranopa; Amirudin Kalbuadi (Epsilon Journal of Management, 2025)
Promoting company products so that they are known to the wider community, not only by promoting through social media or using online media, but promoting directly to the public also has a significant effect on the company's sales volume, such as brochures distributed door to door, through magazines. can be seen directly by the public, through placing banners and banners on every strategic road, this is a marketing strategy that can be used by companies as a tool to introduce their products without having to look on social media or online and there are still many ways that can be used. The aim of this research is to analyze advertising, promotions and personal sales in increasing sales volume at Artshop Sukarara, Central Lombok. The method used in this research is causal associative research, which is asking about the relationship between two or more variables. The location of the research was at the Patuh Sukarara Art Shop, Central Lombpk. The number of respondents in the research was 30 consumers. The results of research on the effectiveness of the promotional mix are thought to have a relationship or relationship with sales volume. Based on the results of analysis of the coefficient of determination (R2), it was found that the coefficient of determination or R-Square value was 0.17906, which means that 17.9% of the dependent variable of sales volume is influenced by advertising and promotion variables. sales, personal sales and public relations, while the rest is explained by unused variables.